2018
DOI: 10.1007/s12402-018-0261-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating attention-deficit/hyperactivity disorder using ecological momentary assessment: a systematic review

Abstract: Ecological momentary assessment is an excellent tool for the measurement of different day-to-day domains in patients and capturing real-world and real-time data. The purpose of this review is to evaluate feasibility in current ecological momentary assessment studies on emotional and behavioral functioning, functional impairments, and quality of life patients with an attention-deficit/hyperactivity disorder diagnosis. This systematic review follows the recommendation of Preferred Reporting Items for Systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 75 publications
2
18
0
Order By: Relevance
“…The mEMA targets identified in this review reflect those reported in previous systematic reviews: affect/mood [7,12,14,15], cognitions [13], symptoms [15], eating or dietary behaviors [10,11], physical activity [10], and smoking or alcohol consumption [5,6]. Likewise, clinical populations identified in this review (psychiatric or mental health conditions, chronic pain and fibromyalgia, eating disorders, and substance use) were generally consistent with those reported previously [5,7,11,12,[14][15][16].…”
Section: Mema Use In Adults For Health-related Behaviors and Psycholosupporting
confidence: 82%
See 1 more Smart Citation
“…The mEMA targets identified in this review reflect those reported in previous systematic reviews: affect/mood [7,12,14,15], cognitions [13], symptoms [15], eating or dietary behaviors [10,11], physical activity [10], and smoking or alcohol consumption [5,6]. Likewise, clinical populations identified in this review (psychiatric or mental health conditions, chronic pain and fibromyalgia, eating disorders, and substance use) were generally consistent with those reported previously [5,7,11,12,[14][15][16].…”
Section: Mema Use In Adults For Health-related Behaviors and Psycholosupporting
confidence: 82%
“…In the last 5 years, there have been at least 10 systematic reviews focused on EMA and/or reporting aspects of compliance to EMA schedules in youth (<18 years [7][8][9]; <22 years [10]), mixed youth and adult cohorts [11][12][13], or specific adult populations [5,[14][15][16]. Compliance with EMA in youth (nonclinical and clinical samples) has been reported to range between 44% and 96% [8][9][10] and in mixed youth and adult cohorts, between 23% and 94% [11][12][13][14]. Reports of compliance in specific adult clinical populations range from 21% to 99% (chronic pain, 21%-99% [15]; psychotic disorders, 78%-86% [16]; substance use, 75%, (95% CI 72.37-77.65) [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, due to recent technical innovations and increased smartphone and sensor use, collecting ambulatory time-series data has become more feasible. The feasibility has been shown for healthy individuals (37), older adults (78,79), and also for patients with psychiatric disorders such as severe depression or bipolar disorder (80), panic disorder (36), psychosis (81), eating disorders (82) or ADHD (83). Data collection via a smartphone is more convenient for the participant than paperand-pencil methods and makes laborious and error-prone data entry unnecessary.…”
Section: Factmentioning
confidence: 99%
“…To the best of our knowledge, there have been no previous systematic reviews that covered the applications of EMA for the study of all youth psychopathology (including both internalizing and externalizing disorders). There have been systematic reviews on the use of EMA for the study of adults with psychopathology (e.g., [13]) or for the study of specific types of psychopathology, regardless of age (e.g., mood disorders [14] and attention-deficit/hyperactivity disorder (ADHD) [15]). In the present review, by considering the broad range of psychopathology in youth, researchers and clinicians can be informed of and inspired by the use of EMA in various fields.…”
Section: Introductionmentioning
confidence: 99%